THE EFFECT OF INDIVIDUAL CHARACTERISTICS AND INTERNAL COMMUNICATION ON EMPLOYEE PERFORMANCE THROUGH WORK ETHOS IN DISTRICT DPRD OFFICE DELI SERDANG - Deby Nanda Sari; Sukaria Sinulingga; Parapat Gultom (CV. Radja Publika, 2023)
Human resources have an important role to support the activities, continuity and success of an organization or agency. Because human resources are the only resources that have reason, feelings, desires, skills, knowledge, encouragement, power, and work. Performance is referred to as an answer to the success or failure of the initial goals of the work program and policies that have been set. Matters regarding performance are very important, because performance is one of the most important measures of organizational quality. One of the factors that influence employee performance is individual characteristics and internal communication. In addition, work ethic is also an important aspect that affects employee performance. The purpose of this research is to analyze the effect of individual characteristics and internal communication on employee performance through work ethic. This research conducted inDeli Serdang Regency DPRD Office with a sample of 102 respondents. Data were analyzed usingdescriptive analysis and SEM (Structural Equation Model) analysis.The results showed that directly individual characteristics had a positive and significant effect on work ethic, internal communication had a positive and significant effect on work ethic, individual characteristics had a positive and significant effect on employee performance, internal communication had a positive and significant effect on employee performance, and work ethic had an effect positive and significant to employee performance. Indirectly individual characteristics have a positive and significant effect on employee performance through work ethic and internal communication have a positive and significant effect on employee performance through work ethic.